2011
DOI: 10.1093/infdis/jir211
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Monovalent 2009 Influenza A/H1N1v Vaccine Adjuvanted With AS03A or Unadjuvanted in HIV-Infected Adults: A Randomized, Controlled Trial

Abstract: Background. Human immunodeficiency virus (HIV)-infected patients have decreased immune response to vaccines. Few data are available about pandemic flu vaccination in this population.Methods. We conducted a multicenter, patient-blinded, randomized trial in a cohort of HIV-infected adults. Patients received 2 injections 21 days apart of a AS03 A -adjuvanted H1N1v vaccine containing 3.75 lg hemagglutinin (HA) or a nonadjuvanted H1N1v vaccine containing 15 lg HA to assess hemagglutination inhibition (HI) response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 18 publications
2
46
2
1
Order By: Relevance
“…We reported recently in HIV-1-infected adults that a twodose schedule of 2009 A/H1N1v vaccine was more immunogenic than a single dose 1 month after the vaccination; moreover, the AS03 A -adjuvanted H1N1v vaccine yielded a higher short-term immune response than the nonadjuvanted vaccine with no impact on HIV infection [6]. We now report the durability of the immune response up to 1 year after vaccination.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…We reported recently in HIV-1-infected adults that a twodose schedule of 2009 A/H1N1v vaccine was more immunogenic than a single dose 1 month after the vaccination; moreover, the AS03 A -adjuvanted H1N1v vaccine yielded a higher short-term immune response than the nonadjuvanted vaccine with no impact on HIV infection [6]. We now report the durability of the immune response up to 1 year after vaccination.…”
Section: Introductionmentioning
confidence: 62%
“…The HIFLUVAC trial was a phase 2, randomized, patient-blinded trial conducted in 18 ANRS-labeled centers in France as described previously [6].…”
Section: Methodsmentioning
confidence: 99%
“…84,85 However, the rate of consequences due to natural A(H1N1) infection was similar between HIV-1 infected subjects and healthy controls and the efficacy of diverse formulations of influenza vaccines (with or without different adjuvants coupled to the influenza antigens) in both adults and children, was reported in several studies. [86][87][88][89] Nonetheless, the numerous studies undergone during the A(H1N1) pandemic represented a great occasion for increasing the knowledge on immunological undetectable HIV-1 viral load and high CD4 + T-cell counts but treated later in time. 36 Altogether, this suggests that early HIV-1 suppression may help preserving the ability of T-and B-cells to respond to DTP in HIV-1 infected children.…”
Section: Adaptive Immune Response To Different Vaccine Typesmentioning
confidence: 99%
“…46,47 Few studies have investigated the clinical efficacy of the influenza vaccine in this population but they agree that the vaccine is clinically effective, with a relative risk reduction of 66 % for the development of symptomatic disease in HIV-infected individuals. 48,49 A randomized trial conducted in Africa in 2008 showed a 75.5% reduction in risk in a population of HIV-infected adults who had a CD4 count >100/mm 3 and no associated co morbidities. 50 A recent systematic review indicates that influenza vaccination is effective in preventing laboratory confirmed influenza infection in HIV-infected adults with a pooled efficacy of 85%.…”
Section: Influenza Vaccinementioning
confidence: 99%